Synthesis and Characterization of ZnO-TiO2/Carbon Fiber Composite with Enhanced Photocatalytic Properties - Bishweshwar Pant; Gunendra Prasad Ojha; Yun-Su Kuk; Oh Hoon Kwon; Yong Wan Park; Mira Park (Nanomaterials, 2020)
Herein, we prepared a novel photocatalytic ZnO-TiO2 loaded carbon nanofibers composites (ZnO-TiO2-CNFs) via electrospinning technique followed by a hydrothermal process. At first, the electrospun TiO2 NP-embedded carbon nanofibers (TiO2-CNFs) were achieved using electrospinning and a carbonization process. Next, the ZnO particles were grown into the TiO2-CNFs via hydrothermal treatment. The morphology, structure, and chemical compositions were studied using state-of-the-art techniques. The photocatalytic performance of the ZnO-TiO2-CNFs composite was studied using degrading methylene blue (MB) under UV-light irradiation for three successive cycles. It was noticed that the ZnO-TiO2-CNFs nanocomposite showed better MB removal properties than that of other formulations, which might be due to the synergistic effects of carbon nanofibers and utilized metal oxides (ZnO and TiO2). The adsorption characteristic of carbon fibers and matched band potentials of ZnO and TiO2 combinedly help to boost the overall photocatalytic performance of the ZnO-TiO2-CNFs composite. The obtained results from this study indicated that it can be an economical and environmentally friendly photocatalyst.